Principles of decentralized public key infrastructure building - Isirova, K.V.; Potii, O.V.; Semenets, V.V. (Radiotekhnika, 2018)
The main principles of building the existing public key infrastructure are given. Problems related to the functioning of such system are described. New concept for public key infrastructure building based on blockchain technology is proposed. Such concept avoids the weaknesses and shortcomings of the hierarchical architecture.